Cities and climate change: How historical legacies shape policy-making in English and German municipalities. (May 2017) - Eckersley, Peter
This article draws on secondary historical sources and primary interviews to highlight how the legacy of the creation of local governments in England and Germany has significant implications for policy-making in the present day. By employing an institutionalist perspective to analyse how one municipality in each country tries to promote renewable energy and retrofit private housing, it demonstrates how historical factors have resulted in the German Council having more capacity to act hierarchically in local governance arrangements than its English counterpart. These findings have notable implications for how governments at all levels seek to tackle major challenges such as climate change.